2008
DOI: 10.1159/000124277
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Otoconia of Osteoporotic Rats

Abstract: The etiology of benign paroxysmal positional vertigo (BPPV) remains obscure in many cases and women are affected more often than men. A recent prospective study, performed in women >50 years of age suffering from recurrent BPPV, showed associated osteopenia or osteoporosis in a large percentage of these patients. These results suggested the possible relationship between recurrent BPPV and a decreased fixation of calcium in bone in women >50 years. To test this hypothesis, an experimental study was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 78 publications
4
74
0
2
Order By: Relevance
“…Finally, high-grade disintegration in the otoconia caused complete dissolution and fragmentation of calcium-rich material to the endolymph, creating the possible underlying cause of symptoms in BPPV. Vibert et al [16] also demonstrated that in ovariectomized rats, osteoporosis induction had created a less dense and less calcium-containing otoconia ultrastructure, which can be attributed to the development of BPPV. In addition to the ultrastructural and animal studies, clinical studies have also investigated the probable relationship between BPPV and calcium metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, high-grade disintegration in the otoconia caused complete dissolution and fragmentation of calcium-rich material to the endolymph, creating the possible underlying cause of symptoms in BPPV. Vibert et al [16] also demonstrated that in ovariectomized rats, osteoporosis induction had created a less dense and less calcium-containing otoconia ultrastructure, which can be attributed to the development of BPPV. In addition to the ultrastructural and animal studies, clinical studies have also investigated the probable relationship between BPPV and calcium metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Otoconia are in a dynamic state, and calcium is required for their mineralization and turnover [23,24]. Calcium and carbonate levels in the endolymph should be kept at critical level to initiate and maintain the mineralization of the otoconia protein matrix and avoid unnecessary mineralization [10,34,36]. It has been suggested that disturbance of calcium metabolism induced by osteoporosis/osteopenia can lead to BPPV.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that degradation and fragmentation of otoconiais an age-related process of demineralization, resulting in balance disorder [34,35]. The presence of osteoporosis or another systemic disease during aging may facilitate otoconial demineralization and detachment from the otoconial bed [34].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the fact that BPPV is more common especially in postmenopausal women aged >50 years, in whom osteopenia and osteoporosis are common. Such studies have suggested that osteoporosis and accordingly the Ca metabolism may be a risk factor for developing BPPV by affecting particularly the peripheral zone in otoconia, which have a similar structure with bone tissue (3). The role of vitamin D, which is directly related to Ca metabolism and bone formation, in BPPV has been concerned and the vitamin D levels of BPPV patients have been investigated.…”
Section: Introductionmentioning
confidence: 99%